2010
DOI: 10.1016/j.compscitech.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical properties of copper–carbon nanofibre composites prepared by spark plasma sintering and hot pressing

Abstract: Several types of carbon nanofibres (CNF) were coated with a uniform and dense copper layer by electroless copper deposition. The coated fibres were then sintered by two different methods, spark plasma sintering (SPS) and hot pressing (HP). The Cu coating thickness was varied so that different volume fraction of fibres was achieved in the produced composites. In some cases, the CNF were pre-coated with Cr for the improvement the Cu adhesion on CNF. The results show that the dispersion of the CNF into the Cu mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Silvain et al [20] studied the thermal conductivity of the CNF/Cu nanocomposite. Ullbrand et al [21] reported the results of the thermo-mechanical properties of the CNF/Cu nanocomposite processed by spark plasma sintering (SPS) and hot press. On the other hand, there have been efforts on the development of the CNF/Al composite, among which, Kwon et al [22] showed that CNFs could be an effective reinforcement material for strength enhancement of pure Al.…”
Section: Introductionmentioning
confidence: 99%
“…Silvain et al [20] studied the thermal conductivity of the CNF/Cu nanocomposite. Ullbrand et al [21] reported the results of the thermo-mechanical properties of the CNF/Cu nanocomposite processed by spark plasma sintering (SPS) and hot press. On the other hand, there have been efforts on the development of the CNF/Al composite, among which, Kwon et al [22] showed that CNFs could be an effective reinforcement material for strength enhancement of pure Al.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuously increasing miniaturization of electronic devices, metal matrix composites (MMCs) applicable for thermal management applications have received increasing attention since an appropriate control of the reinforcement to metal matrix ratio offers excellent tailorability of mechanical and thermal properties [1][2][3]. Recently, the development of aluminum matrix composite has become extremely important owing to its high specific thermal properties (thermal properties divided by density) and ease of machinability.…”
Section: Introductionmentioning
confidence: 99%
“…As explained in the introduction, the main objective of this work has been to use simulation tools to understand why in those cases where it has been possible to produce CNF reinforced Cu matrix composites with a large volume fraction of well dispersed CNFs, the measured thermal properties of the composite have failed to meet the expectations in terms of thermal conductivity, with measured conductivities in the range 100-300 W/m·K [4][5]. To do this, the FEM tools described above were used to carry out a complete parametric study as a function of the thermal anisotropy of the inclusion and the interface conductance to identify the most important factors limiting the real thermal conductivity of this new class of materials.…”
Section: Thermal Conductivity Of the Compositementioning
confidence: 99%
“…However, even in those cases where the experimental difficulties have been overcome and a large volume fraction of well dispersed CNFs has been obtained, the measured thermal properties of the composite have failed to meet the expectations in terms of thermal conductivity [4][5]. There are two possible reasons for this: (1) the highly anisotropic properties of CNFs combined with a preferred orientation of the fibres during processing and (2) the interfacial contact resistance of the Cu-C interface limiting the potential benefit of incorporating these inclusions into the matrix.…”
Section: Introductionmentioning
confidence: 99%